Accreditation Learning Technology and Education Quality in Arabic Language Education Study Program - Karim, Abdul; Nasir, Amin; Al Arif, Irza Maulana; M. Nur, Dany Miftah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Educational technology has become an important factor in improving the quality of higher education, including in the Arabic Language Education Program. With the increasing complexity of accreditation requirements, the use of digital systems, such as Learning Management Systems (LMS) and tracer studies, has become an effective solution for enhancing learning efficiency and evaluating graduates. This study aims to analyze the role of educational technology in supporting academic accreditation and improving graduates' competitiveness in the job market. A quantitative and qualitative research approach was used through surveys and literature reviews. The results showed that the integration of technology in academic processes significantly contributes to learning effectiveness and the accuracy of tracer study data. Additionally, implementing digital systems enables more efficient and transparent management of academic data. Therefore, institutional support in providing infrastructure and technology training is essential to maximize the benefits of digital education and ensure the improvement of educational quality and graduates' competitiveness.